2014
DOI: 10.1016/j.neuroimage.2014.03.077
|View full text |Cite
|
Sign up to set email alerts
|

P300 amplitude variation is related to ventral striatum BOLD response during gain and loss anticipation: An EEG and fMRI experiment

Abstract: The anticipation of favourable or unfavourable events is a key component in our daily life. However, the temporal dynamics of anticipation processes in relation to brain activation are still not fully understood.A modified version of the monetary incentive delay task was administered during separate functional magnetic resonance imaging (fMRI) and electroencephalogram (EEG) sessions in the same 25 participants to assess anticipatory processes with a multi-modal neuroimaging set-up.During fMRI, gain and loss an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
169
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(196 citation statements)
references
References 91 publications
(75 reference statements)
26
169
0
1
Order By: Relevance
“…Also, all studies manipulated (in a different fashion) the success/hit rates of the MIDT by controlling the duration of the target/the time required for a successful response. Most studies (38 of 50) used tasks that had a set success rate of 65–67%, while a minority used a set success rate of 50% (Dillon et al, ; Figee et al, ; Pfabigan et al, ) or 60% (Yau et al, ). Other studies used data from practice trials to inform reaction times, and used a success rates of 40–80% (Bustamante et al, ; Choi et al, ; Costumero et al, ; Jung et al, ; Kirk et al, ; Weiland et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, all studies manipulated (in a different fashion) the success/hit rates of the MIDT by controlling the duration of the target/the time required for a successful response. Most studies (38 of 50) used tasks that had a set success rate of 65–67%, while a minority used a set success rate of 50% (Dillon et al, ; Figee et al, ; Pfabigan et al, ) or 60% (Yau et al, ). Other studies used data from practice trials to inform reaction times, and used a success rates of 40–80% (Bustamante et al, ; Choi et al, ; Costumero et al, ; Jung et al, ; Kirk et al, ; Weiland et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies ascribe reward and loss processing (across both anticipation and receipt) to dissociable neural systems including the ventral striatum, and anterior insula and amygdala, respectively (Hardin, Pine, & Ernst, ; Knutson, Fong, Bennett, Adams, & Hommer, ; Liu et al, ; Yacubian et al, ). Other studies suggest striatal activity is engaged during loss and reward processing, especially their anticipation (Breiter, Aharon, Kahneman, Dale, & Shizgal, ; Carter, Macinnes, Huettel, & Adcock, ; Cho et al, ; Kohls et al, ; Pfabigan et al, ), where midbrain dopamine systems engage during stimulus approach or avoidance (Brooks & Berns, ; Pfabigan et al, ; Salamone & Correa, ). Behavioural and psychological data have also not shown clear distinctions between these processes (Baron & Galizio, ), thus similar neural mechanisms may underlie both.…”
Section: Introductionmentioning
confidence: 99%
“…We admit it is unclear why the effect of sensation seeking diminished when disinhibition levels were higher, but it might be related to the observation that the role of disinhibition in stimulant dependence outweighs that of sensation seeking (Dawe et al, 2004), the theoretical significance of which deserves future investigation. In addition, the key regions in the dopaminergic reward processing system such as the ventral striatum, which play important roles in the neural basis of MID task performance (Joseph et al, 2015; Knutson et al, 2000), might have also contributed to the P3 findings (Pfabigan et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…D. Novak & Foti, 2015). In contrast, Pfabigan et al (2014) reported that the P3 elicited by gain cues was larger than both loss and neutral cues, while the latter two condition showed no difference (see also Vignapiano et al, 2016). Additionally, Pfabigan et al (2015) found that the FRN elicited by the neutral outcome is sensitive to its unexpectedness modulated by cues.…”
mentioning
confidence: 89%
“…This component reflects stimulus categorization processes related to context updating in working memory (Donchin & Coles, 1998; Johnson & Donchin, 1980; see Polich, 2007 for review) and is reliably enhanced for salient stimuli (Polich & Kok, 1995), notably reward cues (Goldstein et al, 2006; Hughes et al, 2013). In support of reward modulation, the cue-P300 for incentive (vs. neutral) cues has been found to covary with activation in the ventral striatum (Pfabigan et al, 2014). As reviewed below, upregulating one’s response to reward cues increases P300-like activity (Langeslag & van Strien, 2013).…”
Section: Introductionmentioning
confidence: 96%